WEBINAR BEDAH BUKU MANAJEMEN PERLINTASAN SEBIDANG (JPMPPI (Jurnal Pengabdian Masyarakat), 2023)
The implementation of a book review webinar entitled "level crossing management" aims to provide insight and knowledge about railroad level crossings to railway stakeholders and the community. Level crossings have always been a complex problem because accidents often occur at level crossings, both official and unofficial level crossings, guarded or unguarded. With the implementation of this book review webinar, it is hoped that railway stakeholders and the general public can understand the management of level crossings starting from legal aspects, traffic control at level crossings, stakeholders and several level crossing guard competencies. This community service was carried out using a web-based seminar technique which was attended by 521 participants through YouTube Channel and Zoom meeting platform that first opened by the Director General of Railways, followed by a presentation by the author, the book was also reviewed directly by the discussants followed by a question and answer session by the participants. All activities are guided directly by the moderator and broadcast live through the Zoom Meeting application and the YouTube channel. The results of this webinar can be used as an enlightenment for railway stakeholders and the community, and it is hoped that they can apply their knowledge to travel safely at railroad crossings.